Cicerón. Catilinarias. Traducción, notas e introducción de Emilio Rollié, Buenos Aires, Ediciones Colihue, 2009. 1º. edición. 336 pp. - Calderón de Puelles, Mariana (2011)
Fil: Calderón de Puelles, Mariana. Universidad Nacional de Cuyo